2013
DOI: 10.1088/0031-8949/2013/t153/014028
|View full text |Cite
|
Sign up to set email alerts
|

Measures of non-Gaussianity for one-mode field states

Abstract: We introduce and investigate a distance-type measure of non-Gaussianity based on the quantum fidelity. This new measure can readily be evaluated for all pure states and mixed states that are diagonal in the Fock basis. In particular, for an Mphoton added thermal state, an analysis of the Bures degree of non-Gaussianity is made in comparison with two previous measures built with the Hilbert-Schmidt metric and the relative entropy. We obtain a compact analytic formula for the Hilbert-Schmidt non-Gaussianity meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 35 publications
3
45
0
3
Order By: Relevance
“…We have shown that decaying of non-Gaussianity was consistently pointed out by three distance-type measures. Thus, the fidelity-based degree, the Hilbert-Schmidt one, and the entropic measure evolve monotonically, as expected for any good measure of non-Gaussianity [9,10]. Moreover, we have compared this evolution to that of the photon-added thermal states which, by contrast, are non-classical.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…We have shown that decaying of non-Gaussianity was consistently pointed out by three distance-type measures. Thus, the fidelity-based degree, the Hilbert-Schmidt one, and the entropic measure evolve monotonically, as expected for any good measure of non-Gaussianity [9,10]. Moreover, we have compared this evolution to that of the photon-added thermal states which, by contrast, are non-classical.…”
Section: Discussionmentioning
confidence: 62%
“…Here we have performed numerically the corresponding summations making use of the probability distributions (2.3) and (3.2). As in the case of a PATS [9], non-Gaussianity of a PSTS increases with the number of subtracted photons. As one can see from Figure 1 of Ref.…”
Section: )(23)mentioning
confidence: 96%
See 2 more Smart Citations
“…a quantum state? Based on the Hilbert-Schmidt distance between ρ and a reference Gaussian state ρ G , we introduce the non-Gaussianity δ[ρ] of a quantum state [41,42] According to the lemmas in Ref. [41,43], we can know that δ[ρ] is a well-defined non-negative quantity and equals zero if and only if ρ is a Gaussian state.…”
Section: B Wigner Function Of the Mr And Non-gaussianitymentioning
confidence: 99%